1985
DOI: 10.1002/bjs.1800720324
|View full text |Cite
|
Sign up to set email alerts
|

Reimplantation of the papilla of Vater

Abstract: Detachment of the papilla of Vater from the duodenum may happen (a) deliberately, during duodenal resection for tumour without concomitant resection of the pancreatic head, and (b) accidentally in the course of gastrectomy for duodenal ulcer, when attempts to exteriorize the ulcer are made. In this report two case histories are cited encompassing both of these circumstances, in which the ampulla was successfully reimplanted into a Roux loop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Williamson et al reported resection of the first and second portions of the duodenum along with a portion of the pancreatic head. The ampulla was anastomosed to a Roux loop [9]. Fleisch reported resection of the first and second portions of the duodenum with detachment of the ampulla.…”
Section: Discussionmentioning
confidence: 99%
“…Williamson et al reported resection of the first and second portions of the duodenum along with a portion of the pancreatic head. The ampulla was anastomosed to a Roux loop [9]. Fleisch reported resection of the first and second portions of the duodenum with detachment of the ampulla.…”
Section: Discussionmentioning
confidence: 99%